NMR characterization of hydrate and aldehyde forms of imidazole-2- carboxaldehyde and derivatives - Lazaro Martinez, Juan Manuel (2010)
The existence and stability of the aldehyde-hydrate form of imidazole-2-carboxaldehyde (4) were studied using FTIR together with solution- and solid-state NMR experiments. The results allowed us to conclude that the hydrate form was stable and precipitated at pH = 8.0 and that the aldehyde form was isolated at pH = 6.5 and 9.5. Moreover, the presence of the aldehyde-hydrate form was studied through NMR experiments in D2O at both alkaline and acidic pH. In addition, the tautomeric forms of the 2-substituted imidazole compounds were also analyzed to investigate the influence of the hybridization on the carbon adjacent to the imidazole ring, by 13C NMR in DMSO-d6, acetone-d6, and CDCl3. The presence of the syn- and anti-isomers of oxime 8 obtained from 4 were characterized by solid-state NMR and variable-temperature NMR experiments in acetone-d 6.